Vocabulary: Description, Acquisition and Pedagogy - Schmitt N. Norbert; McCarthy M. Michael (Cambridge Language Teaching Library)
The book's fifteen chapters are grouped together to achieve a balanced coverage of descriptions of what vocabulary is and how it behaves, how the mind learns new vocabulary and then uses it when it is learned, and pedagogical issues of teaching and testing second language vocabulary. me of the specific topics addressed in these three general areas include: word frequency and vocabulary size, multi word units, variation between spoken and written language; models of lexical acquisition, first language influences on second language vocabulary acquisition, vocabulary learning strategies: vocabulary and the syllabus, trends in teaching vocabulary, testing vocabulary, lexical reference resources. All the contributors are leading authorities in their respective areas and the editors have provided an introductory overview to the book and commentaries on the chapters.